Patients' Use and Perception of Internet-Based Orthopaedic Sports Medicine Resources. Issue 9 (19th September 2018) - Koenig, Scott; Nadarajah, Vidushan; Smuda, Michael P.; Meredith, Sean; Packer, Jonathan D.; Henn, R. Frank
Background: Current research is sparse regarding how patients with orthopaedic injuries perceive and use internet-based information resources. Hypothesis: The majority of patients use the internet to research their orthopaedic condition and are receptive to guidance from their provider. Study Design: Cross-sectional study. Methods: A total of 213 patients attending a sports medicine clinic on the East Coast of the United States were asked to complete a questionnaire regarding their use of internet-based information. Data from 185 patients were available for analysis. Bivariate and multivariate statistical analyses were used to determine the significance of identified associations. Results: Overall, 54% of patients used the internet to find information about their orthopaedic condition prior to their consultation. A higher percentage of internet users were women ( P = .01), were white ( P = .03), and had internet access at home ( P = .02). Multivariable analysis found home internet access to be the only significant independent factor predictive of patients using internet-based information sources ( P < .01). The majority of patients (61%) were neutral toward orthopaedic information found online, and only 32% of patients trusted the orthopaedic information they found online. The majority of patients (83%) reported they would be receptive to providers' guidance on which internet resources to use. Conclusion: Only half of patients use the internet to research their orthopaedic condition. Most patients were either neutral toward or did not trust the internet-based information that they found and may forgo internet sources altogether. To help patients avoid misleading information, sports medicine providers should understand how patients are using the internet and guide patients in selecting high-quality, peer-reviewed sources of information. Doing so allows physicians to proactively educate their patients even after the clinic visit.